Analysis of the potential behavioral impact of methanol when used as a solvent: Dataset from zebrafish (Danio rerio) behavioral research - Hamilton, Trevor; Szaszkiewicz, Joshua; Krook, Jeffrey T.; Burggren, Warren (My University, 2021)
Toxicants are commonly administered to experimental organisms using solvents as vehicles. One common vehicle for dissolving toxicants is methanol (CH3OH), a solvent which on its own is capable of altering physiology and behavior high concentrations. This dataset describes behavioral results in zebrafish (Danio rerio) individually exposed to methanol (0.25%, 2.5% vol/vol), or control water, for 30 min prior to behavioral testing. Zebrafish were placed into an open field arena to examine locomotion and zone preference, which was recorded and quantified with motion-tracking software (EthoVision XT). Time spent in the outer (“thigmotaxis”) zone of the arena is a proxy for increased anxiety-like behavior in zebrafish. Additionally, a novel object was placed into the center of the arena to quantify relative increases in boldness/exploration between the methanol and control groups. There were no differences in time spent in any zone of the arena or distance travelled between either group, in either test.
Keywords: methanol; solvents; vehicles; behavioral neuroscience; zebrafish; open field test; novel object approach test